If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6 = 3x + -7 Reorder the terms: 6 + 2x = 3x + -7 Reorder the terms: 6 + 2x = -7 + 3x Solving 6 + 2x = -7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 6 + 2x + -3x = -7 + 3x + -3x Combine like terms: 2x + -3x = -1x 6 + -1x = -7 + 3x + -3x Combine like terms: 3x + -3x = 0 6 + -1x = -7 + 0 6 + -1x = -7 Add '-6' to each side of the equation. 6 + -6 + -1x = -7 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = -7 + -6 -1x = -7 + -6 Combine like terms: -7 + -6 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13
| -10n+3(8+8n)+3=6 | | p(2+w)-4w=3w-10 | | -3+12=48 | | 11(1p-3)=5(1p+3) | | 48n^2=6n | | 11+6x+4x=31 | | 9=-5x+2(x+3) | | 5c-4(2c+1)=8c+2 | | a-4.75=1.85 | | 17.25+x=12.95+15x | | 28=-2(k-6) | | m+6.50=1.30 | | 3x-35=-20 | | 2(3x+4)=18 | | -4x+7x=-9 | | -8-y=-4 | | 3p+12=18 | | 60x+35=y | | 4+a=-(a-6) | | 3-x=243 | | log(5)25=4x+9 | | 3.2k-43=12.6k+14.5 | | 3x^2+39=-21x | | (3x+2)+(2x+13)=180 | | 2x^2+361x-64=0 | | 7x-21y+14= | | 2+2x=73 | | 8=-5+-b | | 45=4x+1 | | X-8=10+2 | | 12+5x-2x=4 | | (5x-2)(x-2)=0 |